PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Ayub Muslih Ayub; Muhammad Nuryatno Amin (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The purpose of this study was to examine the effect of profitability, capital structure and firm size on firm value. In the companies financial sector in the banking sub-sector listed on the Indonesia Stock Exchange (IDX). The independent variables used in this study are profitability, capital structure and firm size. While the dependent variable used in this study is firm value. The data used is secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period, the research sample is 43 companies selected using the purposive sampling method. The method used to analyze the relationship between variables in this study is multiple linear regression analysis. And the analytical method used for hypothesis testing is SPSS. Based on the results of this study indicate that profitability, capital structure and firm size partially and simultaneously have a positive effect on firm value. the higher the level of profitability, the level of debt that is within reasonable limits and the size of the company will affect the value of the company.